Perbedaan Gender dalam Persepsi Citra Tubuh dan Status Gizi pada Remaja di Kabupaten Sangihe, Indonesia: Studi Potong Lintang - Ferdinand Gansalangi; Meityn Disye Kasaluhe (An Idea Health Journal, 2026)
Background: Adolescents in Indonesia experience a dual burden of malnutrition. Body image perception during adolescence can contribute to unhealthy eating behaviors. However, limited evidence exists regarding body image and its association with nutritional status in Indonesia’s island communities. This study analyzes differences in body image perception and nutritional status by gender, age group, and Body Mass Index (BMI) among adolescents in Sangihe District, Indonesia Methods: The cross-sectional study was conducted from October 2025 to March 2026 and included 787 adolescents aged 10–18 years, selected through convenience sampling from accessible schools across the island. Result: Most respondents exhibited normal nutritional status (68.7%), while 23.6% were overweight and 7.6% were underweight. No significant differences were observed in body image scores (p=0.731) or BAZ values (p=0.831) between males and females. A significant difference in body image scores was found between the puberty and post-puberty age groups (p=0.013). No significant differences in body image scores were identified across nutritional categories (p=0.866). Conclusion: In this island context, puberty appears to be a more influential factor in body image than gender or nutritional status. These findings underscore the importance of holistic,developmentally sensitive, and gender-inclusive health promotion programs tailored to the unique context of adolescents on Indonesian islands.